Effect of a gel containing green tea extract and hyaluronic acid on palate pain scores and wound healing after free gingival graft: a quasi-randomized controlled clinical trial - Oliveira, Jovânia Alves (2023)
Objectives: The aim of this study was to evaluate the effect of a gel containing green tea extract and hyaluronic acid (HA) on pain scores and wound healing in donor sites after free gingival graft (FGG). Materials and methods: Forty-two patients requiring FGG were included in three groups: (1) control group (n = 14), no material was placed in the donor area; only the clot was kept in position by sutures; (2) placebo group (n = 14), vehicle gel applied 3 times a day for 7 days; and (3) test group (n = 14), gel containing green tea extract and HA applied 3 times a day for 7 days. The wound size by clinical measurement (WS-CM) and photographic image (WS-PI), complete wound epithelialization (CWE), and palatal mucosa color were evaluated after 3 days and 1, 2, and 4 weeks postoperatively. The visual analog scale (VAS) for pain and analgesic consumption were used to assess participant’s perception in the same postoperative periods. Results: A similar progressive reduction in the wound size, associated with an improvement in the color pattern, was observed in all groups (p > 0.05). No significant differences were found for CWE and pain assessment between the examined groups (p > 0.05). Conclusion: The gel containing green tea extract and HA application in palatal wounds after FGG removal does not provide clinical healing benefits using this investigated protocol. Clinical relevance: This is the first clinical study evaluating the effect of gel containing green tea extract and HA on the palate postoperative pain control and wound healing after FGG. Trial registration: http://clinicaltrials.gov : NCT05270161